Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea) - Greenwalt, Dale E.; Blagoderov, Vladimir A. (Zootaxa, 2019)
The dipteran family Bolitophilidae, with the single extant genus Bolitophila, is a small family of mycophagous flies. In marked contrast to related families such as Sciaridae and Mycetophilidae, the family has a poor fossil record with no definite species assigned to the genus. In addition, the position of the extinct Cretaceous subfamily Mangasinae Kovalev, 1986 (described in Bolitophillidae) has been controversial and it has been suggested that species in this clade may belong to other sciaroid families. This situation is made worse by misplacement of the type specimen. We herein describe two new species of Bolitophila, Bolitophila warreni sp. nov. from the 46-million-year-old Kishenehn Formation in Montana, USA and Bolitophila rohdendorfi sp. nov. from Baltic amber. Bolitophila pulveris Lewis, 1969 is reassigned to Sciaroidea incertae sedis. The subfamily Mangasinae is reviewed and its position within the Bolitophilidae confirmed. Two new species of Mangas, M. kovalevi sp. nov. and M. brevisubcosta sp. nov., both from the Lower Cretaceous of Khasurty in Western Transbaikalia, are described.